The type 1 diabetes resistance locus B10 Idd9.3 mediates impaired B‐cell lymphopoiesis and implicates microRNA‐34a in diabetes protection. Issue 6 (29th April 2014) - Berry, Gregory J.; Budgeon, Lynn R.; Cooper, Timothy K.; Christensen, Neil D.; Waldner, Hanspeter
<x xml:space="preserve">Abstract</x> NOD.B10 Idd9.3 mice are congenic for the insulin‐dependent diabetes (Idd) Idd9.3 locus, which confers significant type 1 diabetes (T1D) protection and encodes 19 genes, including microRNA (miR)‐34a, from T1D‐resistant C57BL/10 mice. B cells have been shown to play a critical role in the priming of autoantigen‐specific CD4+ T cells in T1D pathogenesis in non‐obese diabetic (NOD) mice. We show that early B‐cell development is impaired in NOD.B10 Idd9.3 mice, resulting in the profound reduction of transitional and mature splenic B cells as compared with NOD mice. Molecular analysis revealed that miR‐34a expression was significantly higher in B‐cell progenitors and marginal zone B cells from NOD.B10 Idd9.3 mice than in NOD mice. Furthermore, miR‐34a expression in these cell populations inversely correlated with levels of Foxp1, an essential regulator of B‐cell lymphopoiesis, which is directly repressed by miR‐34a. In addition, we show that islet‐specific CD4+ T cells proliferated inefficiently when primed by NOD.B10 Idd9.3 B cells in vitro or in response to endogenous autoantigen in NOD.B10 Idd9.3 mice. Thus, Idd9.3‐encoded miR‐34a is a likely candidate in negatively regulating B‐cell lymphopoiesis, which may contribute to inefficient expansion of islet‐specific CD4+ T cells and to T1D protection in NOD.B10 Idd9.3 mice.